KARAKTERISTIK PENDERITA DEMAM TIFOID YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2016 - Mai Debora Gultom; Jemadi .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Typhoid fever is a systemic infection caused by Salmonella Typhi, usually by consuming of food and water that has been contaminated. WHO (2003) notified there were 17 million typhoid fever cases with CFR 3,5 %. In 2008, typhoid fever cases hospitalized in North Sumatera hospital were 10.80%. The aims to identify characteristics of  Tifoid Fever patient. This is a descriptive study with case series design. The population of this study was 739 patients with 259 data sample was taken by Simple random sampling. Univariate analysis descriptive and bivariate analysis used Chi-Square test, Fisher test, and Mann Whitney test. Patients of Typhoid Fever The are age 5-14 years 31.3%, women 57,5% ,bataknese 93,4%, Protestant 70,3%,  student/student college 45,9 %, unmarried 71.8%, Medan city 73%, fever 100%, Tubex test  4  (72,6%) and 6 (27,4%), no complication 95,4%, Bronchopneumonia 75%, not their own cost 67,2%, time of hospitalization around 4,39 days, and go home and recover 97,3%. There was difference of sex proportion based on the complication status (p = 0,954), the sources of cost proportion based on complication status (p=0,111), the time of hospitalization proportion based on the source of cost (p = 0.001), the time of hospitalization proportion based on the condition while of home (p = 0.004). It is Expected for patient with Typhoid Fever to maintain the hygiene of food and drink consumed. For Santa Elisabeth Medan is expected to complete the patient medical record and for patient is cured to be advised to do bacteriological check again until cured completely.   Key words: Characteristics, Typhoid Fever, Santa Elisabeth Hospital Medan